Influence of pavement condition towards accident number on Malaysian highway - Baskara, S. N.; Haryati, Yaacob; Mohd Rosli, Hainin; S. A., Hassan; Nordiana, Mashros; N. Z. M., Yunus; N. A., Hassan; Muhammad Naqiuddin, Mohd Warid; M. K., Idham; C. R., Ismail; H. M., Nor; A., Mohamad; et al. (IOP Science, 2019)
Accidents in Malaysia are alarming and have been in the rise for the past decades. Increasing numbers of road users, condition of road surface, expanded road network and weather conditions are being carefully looked into determining the contributors towards fatality. Human factors has been widely known and established as one of the main contributor to road accidents. Therefore, this study had focused more on to pavement conditions, where its relation with accidents needs to be further explored. The purpose of this study is to determine the influence of pavement condition towards accident number on Malaysian Highway. Pavement condition data which consist of Mean Texture Depth (MTD), Rutting Depth (RD) and also International Roughness Index (IRI) were measured along 265 km southern stretch of Malaysia highway, by using Multi Laser Profiler (MLP). Accident data were also collected from the accident report prepared by Southern region of Malaysian Highway Authority. Based on the results, it was found that more than 70% of the accidents happened at a good condition of road which having high MTD, low RD and minimum IRI. MTD was found as the most significance parameters that relates to accident. Other factors such as human negligence and environments (weather and lighting), might be the major cause that contribute to the accidents that happened along Malaysian highway.